RADIOGRAPHIC COMPARISON OF OBTURATION PERFORMED BY CONVENTIONAL METHOD AND OBTURA II - Jadoon, Sheejia Asif; Shehrayar Akhtar Khokhar; Aqsa Waheed; Samia Ejaz; Ahsen Amin; Abdal Hidayat (Journal of Ayub Medical College Abbottabad, 2023)
Background: Preventing tooth loss is of utmost importance in maintaining optimal mastication, phonation, and aesthetics. Most commonly, pulpitis occurs as a result of caries, while trauma less frequently causes it. In both cases, it can lead to unbearable pain. To alleviate this pain and preserve the tooth without resorting to extraction, root canal treatment is indicated. To compare the radiographic quality of root canal filling sealing achieved with the Obtura II system and the cold lateral condensation technique. Methods: This randomized clinical trial was conducted at the School of Dentistry with a total of 260 participants. The study focused on single-rooted teeth that required endodontic treatment. Group A was assigned the cold lateral condensationwhile Group B received obturation using the Obtura II system. A radiographic assessment was performed to evaluate the presence of voids and the extent of extension at the apex in both groups. The chi-square test was utilized to compare the occurrence of voids and the extent of extension between the two groups. Results: In the Cold Lateral Compaction cold lateral condensation group, 113 cases (86.92%) achieved optimum extension, while in the Obtura II group, 114 cases (87.69%) achieved the same. A statistically significant difference was observed between the groups in terms of extension (p=0.033). Although the difference in extension quality was not statistically significant, it is worth noting that the Obtura II group had a higher incidence of overextension. The cold lateral condensation group had 104 cases (80.00%) with no voids, whereas the Obtura II group had 121 cases (93.08%) without voids. A statistically significant difference was observed between the groups regarding the presence of voids (p=0.004). Conclusion: Obtura II exhibits a denser sealing and fewer voids compared to the cold lateral condensation technique. However, Obtura II showed a slightly higher tendency to extend beyond the apex compared to the CLC technique.